Low Latency Evaluation of an Adaptive Industrial Wireless Communications System for ISM Bands - Kloc, Matej; Franchi, Norman; Gardill, Markus; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2016)
Low latency and highest transmission reliability are the key challenges for enabling time-critical industrial wireless applications, e.g. in factory automation. Both are significantly determined by the rough and dynamic environmental conditions as well as regulatory limitation of spectrum access in unlicensed frequency bands, especially in the 2.4 GHz industrial, scientific and medical (ISM) band. In order to get these influences under control, a novel concept for an adaptive and low latency (≤ 1 ms) industrial wireless communications (IWC) system that adopts a robust IEEE 802.11p physical layer (PHY) is proposed and evaluated. Based on representative coexistence measurements in a real environment, the results of extensive simulations and analysis are shown in order to evaluate achievable latencies.
elib2cris::1512001600,kloc2016a